THE USE OF SPELLING BEE METHOD TO IMPROVE STUDENTS’ ENGLISH VOCABULARY FOR EIGHT GRADE STUDENTS OF SMP NEGERI 17 MARUSU - Sardiansa S; Muthmainnah Mursidin; Rizka Indahyanti (ADHILINGUA: Journal of Language Education, Lilnguistics and Literature, 2025)
This study aims to analyze the effectiveness of the Spelling Bee method in improving English vocabulary mastery of eighth grade students at SMP Negeri 17 Marusu. This study uses a quantitative approach with a pre-experimental design, namely one-group pretest-posttest. A total of 25 students of class VIII.a were selected as research samples. Data were collected through vocabulary tests before and after treatment, and analyzed using the Wilcoxon Signed Rank Test. The results of the study showed a significant increase in students' vocabulary mastery after the Spelling Bee method was implemented. The average pretest score of students was 80.80, while the average posttest score increased to 98.00. The results of the statistical analysis showed a significance value of 0.000 (p <0.05), so the null hypothesis (H?) which states that "there is no significant difference in vocabulary improvement before and after treatment" is rejected. Conversely, the alternative hypothesis (H?) which states that "there is a significant difference in vocabulary improvement before and after treatment" is accepted. In addition, this method also increases students' motivation and participation in learning English. Thus, the Spelling Bee method can be considered as an effective learning strategy to improve students' English vocabulary mastery.